Allogeneic hematopoietic cell transplantation in T-cell prolymphocytic leukemia: A single-center experience. (April 2018) - Dholaria, Bhagirathbhai R.; Ayala, Ernesto; Sokol, Lubomir; Nishihori, Taiga; Chavez, Julio C.; Hussaini, Mohammad; Kumar, Ambuj; Kharfan-Dabaja, Mohamed A.
Highlights: Allogenic cell transplantation is effective therapy for patients with T-cell Prolymphocytic Leukemia. Non-relapse mortality and relapse remain limitations of transplant efficacy. Post-transplant strategies may help to further improve outcomes. Abstract: Background: T- cell prolymphocytic leukemia (T- PLL) is a rare aggressive hematological malignancy. Alemtuzumab, an anti-CD52 humanized monoclonal antibody, is the treatment of choice for remission induction. Allogeneic hematopoietic cell transplantation (allo-HCT) has been described to induce durable remissions and improve survival, but data is limited. Patients and methods: We evaluated clinical outcomes of 11 patients, median age of 56 (range, 43–71) years who underwent allo-HCT for T-PLL. The majority of cases were in the first complete remission (CR1 = 9, CR2 = 1, second partial response PR2 = 1) at time of allo-HCT. Myeloablative conditioning was the most commonly prescribed preparative regimen (n = 8, 73%) and tacrolimus plus sirolimus was most commonly prescribed regimen for graft-versus-host disease prophylaxis (n = 5, 46%). Results: The median follow-up for surviving patients was 48 (range, 6–123) months. The 4-year progression-free survival (PFS) and overall survival (OS) were 45% (95% confidence interval (CI) = 13–78%) and 56% (95% CI = 24–89%), respectively. Cumulative incidence of non-relapse mortality (NRM) at 4-year post-transplantation was 34% (95%CI = 14–85%). The 4-year cumulative incidence of relapse/progression was 21% (95% CI = 6–71%). Conclusion: Allo-HCT is an effective treatment for T-PLL. Patients must be evaluated for their candidacy for allo-HCT as soon as the diagnosis is confirmed. Efforts are needed to decrease NRM and relapse.